SLT and CLL in the ELT Classroom: Revisited - Naumoska, Aneta (Pavilion Publishing and Media Ltd, 2025)
What is the continuing influence of Situational Language Teaching (SLT) and Community Language Learning (CLL) in the modern ELT classroom and how do they connect to second language acquisition (SLA) theories? Where SLT strongly emphasises oral practice, grammar and sentence patterns, CLL offers specific techniques based on counselling rather than a method in its own right.
Keywords: SLT; CLL; ELT; SLA